Engineering Leaf-Like UiO-66-SO3H Membranes for Selective Transport of Cations - Xu, Tingting; Shehzad, Muhammad Aamir; Wang, Xin; Wu, Bin; Ge, Liang; Xu, Tongwen (Nano-Micro Letters, 2020)
Metal–organic frameworks (MOFs) with angstrom-sized pores are promising functional nanomaterials for the fabrication of cation permselective membranes (MOF-CPMs). However, only a few research reports show successful preparation of the MOF-CPMs with good cation separation performance due to several inherent problems in MOFs, such as arduous self-assembly, poor water resistance, and tedious fabrication strategies. Besides, low cation permeation flux due to the absence of the cation permeation assisting functionalities in MOFs is another big issue, which limits their widespread use in membrane technology. Therefore, it is necessary to fabricate functional MOF-CPMs using simplistic strategies to improve cation permeation. In this context, we report a facile in situ smart growth strategy to successfully produce ultrathin (< 600 nm) and leaf-like UiO-66-SO3H membranes at the surface of anodic alumina oxide. The physicochemical characterizations confirm that sulfonated angstrom-sized ion transport channels exist in the as-prepared UiO-66-SO3H membranes, which accelerate the cation permeation (~ 3× faster than non-functionalized UiO-66 membrane) and achieve a high ion selectivity (Na+/Mg2+ > 140). The outstanding cation separation performance validates the importance of introducing sulfonic acid groups in MOF-CPMs. Highlights: 1 Ultrathin (< 600 nm) and defect-free leaf-like UiO-66-SO3H membranes were fabricated via in situ smart growth. 2 The sulfonated angstrom-sized ion transport channels in the membranes could accelerate the cation permeation (~ 3× faster than non-functionalized UiO-66 membrane) and achieve a high ion selectivity (Na+/Mg2+ > 140).